"How Come You Are Here?" Considering the Context in Research on Travel Decisions. (February 2019) - Beritelli, Pietro; Reinhold, Stephan; Luo, Jieqing
Travel decision research still struggles to explain a large portion of the variance in travel choices. We argue that advances in this domain must originate from a shift in the kinds of questions we ask travelers to understand what triggers their decisions. The proposed shift from "Why did you . . . ?" to "How come . . . ?" changes the emphasis from retrospective sense giving to a contextual understanding of travel choice, focusing in particular on the constellations that produce actual travel behavior. This shift opens research avenues of a new theoretical and methodological nature and has fundamental implications for consumer research as well as destination marketing practices.